Quality Assessment Tool within Systematic Reviews in Pediatric Dentistry in the Last Decade: Understanding the Threshold - Joe Mathew Cherian; Alpana Kumari; Mebin George Mathew; Nebu Philip (Journal of South Asian Association of Pediatric Dentistry)
Background: Numerous risk-of-bias tools are available to evaluate the quality of primary studies included in a systematic review (SR). Aim: This study aimed to assess the prevalence of such tools in SRs within the field of pediatric dentistry and to explore whether a threshold for methodological quality has been implemented when selecting primary studies for inclusion. Materials and methods: A comprehensive electronic search was conducted across seven pediatric dentistry journals to identify SRs published between 2012 and 2023. The use, type, and extent of quality assessment tools applied in the SR process, along with the presence of a methodological quality threshold set by the authors, were analyzed. Results: Among the 198 SRs that met the inclusion criteria, 37 quality appraisal and risk-of-bias tools were used either individually or in combination. In this sample, only one-tenth (21/198; 10.6%) of the SRs included a defined threshold for the quality of primary studies. When considering only SRs with meta-analyses (MA), this percentage increased slightly to 17.3%. Conclusion: SRs in pediatric dentistry employ a variety of quality assessment tools to evaluate primary studies; however, only one-tenth of them included a defined threshold for the quality of the studies. The scientific community should adopt stricter reporting standards to enhance the quality of SRs, thereby ensuring that their findings can be effectively translated into clinical practice.